PRESENTATION OF THE MULTICENTRIC COLLECTION SPINE SURGERY DATABASE - Pokorny,Gabriel (2022)
ABSTRACT Objectives: To present the Spine Surgery Database developed by the Brazilian Spine Study Group and the methodology involved in its creation, in addition to presenting initial informationabout the use of the database. Methods: Description of the steps for selecting the questionnaires and variables to be included in the database, initial expansion of the use of the database tophysicians close to the BSSG, a brief exploration of quality control and methods for the inclusion ofnew centers, and training on the database, in addition to a brief descriptionof some of the data included in the database. Results: Currently, the database includes 428 patients who already underwent spine surgery and 9 collection centers with at least one patient collected. Conclusion: The Brazilian Spine Study Group’s Multicentric Collection Database is a viable tool that allows patients from different sourcesto be included within a common flow. Level of Evidence V; Expert opinion.